QUEST III : an estimated DSGE model of the euro area with fiscal and monetary policy - Ratto, Marco; Roeger, Werner; Veld, Jan in't 1962-; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : European Comission : Directorate-General for Economic and Financial Affairs, 2008)
This paper develops a DSGE model for an open economy and estimates it on euro area data using Bayesian estimation techniques. The model features nominal and real frictions, as well as financial frictions in the form of liquidity constrained households. The model incorporates active monetary and fiscal policy rules (for government consumption, investment, transfers and wage taxes) and can be used to analyse the effectiveness of stabilisation policies. To capture the unit root character of macroeconomic time-series we allow for stochastic trend in TFP, but instead of filtering data prior to estimation, we estimate the model in growth rates and stationary nominal ratios.
Economic Papers.